Mütoloogiline tegelane tšokmor udmurtide traditsioonilises maailmavaates - Galina Glukhova (Mäetagused)
Based on linguistic data and ritual practices of the Udmurts, the article explores the etymology of the word chokmor. The analysed material indicates that the term chokmor/chokmorskon is used in the local traditions of both southern (Kiyasovo district) and northern (Kez district) Udmurts during winter and spring-summer ceremonies. The study of the term chokmor in the traditional worldview of the Udmurts allows for the hypothesis that the word is derived from the term chek or cheke, and in this context, in the rituals of commemoration, it serves as a symbol of contact with the otherworldly realm. In the rituals of spring and winter masquerades, it personifies the soul of a deceased ancestor, “appearing” in this world in the form of a masqueraded character.